2014
DOI: 10.1080/09540121.2014.906555
|View full text |Cite
|
Sign up to set email alerts
|

Does investment in home visitors lead to better psychological health for HIV-affected families? Results from a quasi-experimental evaluation in South Africa

Abstract: Children and families affected by HIV are at considerable risk for psychological distress. Community-based home visiting is a common mechanism for providing basic counseling and other services to HIV-affected families. While programs emphasize home visitor training and compensation as means to promote high-quality service delivery, whether these efforts result in measurable gains in beneficiaries' well-being remains largely unanswered. This study employs a longitudinal quasi-experimental design to explore whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Among the home visiting programs, Sherr and colleagues (2016) found CBO attenders had lower depression, suicidal ideation, and peer and conduct problems, and greater prosocial behaviors relative to a control group of non-CBO attenders. However, evaluations by Thurman et al (2014) and Visser et al (2015) found null effects for child mental health, and Zuilkowski and Alon (2015) found improvements in child psychosocial scores from Wave 1 to 2 (first year of programming) but not from Wave 2 to 3 (years 2-3 of programming). In summary, there were mixed effects for home visiting programs on child mental health.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Among the home visiting programs, Sherr and colleagues (2016) found CBO attenders had lower depression, suicidal ideation, and peer and conduct problems, and greater prosocial behaviors relative to a control group of non-CBO attenders. However, evaluations by Thurman et al (2014) and Visser et al (2015) found null effects for child mental health, and Zuilkowski and Alon (2015) found improvements in child psychosocial scores from Wave 1 to 2 (first year of programming) but not from Wave 2 to 3 (years 2-3 of programming). In summary, there were mixed effects for home visiting programs on child mental health.…”
Section: Resultsmentioning
confidence: 93%
“…Other evaluations evaluated outcomes post-intervention (Bell et al, 2008), 2 weeks post-intervention (Bhana et al, 2014), 1 and 3 months post-intervention (Puffer et al, 2016), 3 months post-intervention (Thurman et al, 2018), after 12-and 15-months of programming (Sherr et al, 2016), and after 2 (Thurman, Kidman, & Taylor, 2014) Local Cultural Adaptation and Community Participation. Six of ten interventions included in this review were of programs developed by researchers (Bell et al, 2008;Bhana et al, 2014;Eloff et al, 2014;Puffer et al, 2016;Thurman et al, 2018;Ward et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations